Energy costs for cutting soil with disks analysis - V. A. Nikolaev (Вестник СибАДИ, 2022)
Introduction. When designing a unit for the formation of the underlying layer, the problem arose of choosing working bodies designed for preliminary loosening of the surface layer of soil saturated with plant roots, with the aim of subsequent exposure of the underlying layer of the road under construction. When choosing the working bodies of technical means, many factors should be taken into account. However, the decisive indicator is the energy consumption per unit volume of the material being processed. Although the theoretical foundations of cutting soil are considered in great detail, but based on them it is difficult to identify and compare energy costs per unit volume of the developed soil. Options for determining the active forces and energy costs for cutting soil with disks, outlined by various authors, suggest the solution of very cumbersome dependencies. They are based on a synthesis approach to solving the problem. Without rejecting the synthesis approach, an analysis of the interaction of disks with the soil is made. Calculation of energy costs of disk ripper is carried out on the basis of previously identified values of its geometric, kinematic and dynamic parameters.The method of research. Based on the structural layout of the disc ripper, the distance and time of movement of the disc ripper for the development of soil with a volume of one cubic meter was determined. For analysis, the disc is divided into elements: the edge of the blade, the chamfer of the blade and the side surfaces of the disc. A method for determining energy costs has been developed: for separating the soil layer from its array, dividing the layer into fragments, overcoming the soil pressure on the chamfer of the disk, accelerating the soil with a chamfer of the disc blade, overcoming friction between the soil and the chamfer of the disc blade, overcoming friction between the soil and the side surface of the disk. A scheme of conditional forces of influence of a chamfer of a blade of a disk on a ground for determination of conditional normal reaction of a chamfer of a blade of a disk and scheme of forces from determination of normal reaction of a lateral surface of a disk on influence of a ground is developed. The energy costs of cutting the roots with the edge of the blade of the disc can only be determined by experiments.Results. On the basis of the developed methodology, energy costs have been determined: for separating the soil layer from its array, dividing the layer into fragments, overcoming the ground pressure on the chamfer of the disk, accelerating the soil with the chamfer of the blade of the disk, overcoming friction between the soil and the chamfer of the blade of the disk, overcoming friction between the soil and the side surface of the disk. From the scheme of the conditional forces of the impact of the chamfer of the blade of the disk on the ground, the conditional normal reaction of the chamfer of the blade of the disc is determined. From another scheme of forces, the normal reaction of the lateral surface of the disc to the effects of the soil was revealed. The total volumetric energy costs for cutting soil with disks are obtained by adding the identified partial energy costs.Conclusion. On the basis of the theoretical studies carried out, the volumetric energy costs for cutting the soil with disks have been calculated. To these it is necessary to add energy costs: for cutting the roots with the edges of the blades of the disks and for moving the disc ripper. The structure of known energy expenditure is dominated by the energy to overcome friction between the soil and the side surface of the disk. Since the energy costs for cutting soil with disks are very high, it is impractical to use them in the unit for the formation of the underlying layer. This does not exclude the use of disc rippers for other purposes.